AI-Assisted Feedback in EFL Academic Writing: Evidence from Indonesian Pre-Service English Teachers - Ardian, Fahrur; Brinda, Sonya; Zakiya, Lus Firdaus; Hidayatullah, Muhammad Ridwan (Journey: Journal of English Language and Pedagogy, 2026)
The integration of artificial intelligence (AI) in language learning has created new opportunities for improving students’ writing skills through immediate and personalized feedback. This study investigated the effectiveness of AI-assisted feedback in enhancing EFL academic writing among Indonesian pre-service English teachers and explored their perceptions of its use. An explanatory sequential mixed-methods design was employed involving 60 students enrolled in an academic writing course. Quantitative data were collected through pre-test and post-test writing assessments administered to an experimental group receiving AI-assisted feedback and a control group receiving conventional lecturer feedback. Qualitative data were gathered through semi-structured interviews with selected participants from the experimental group. The findings revealed that the experimental group achieved significantly greater improvement in writing performance than the control group, particularly in grammar, organization, and vocabulary. Interview results indicated that students perceived AI-assisted feedback as useful, accessible, and supportive of their writing development. The participants also reported increased confidence and greater engagement in the revision process. However, concerns regarding excessive dependence on AI were also identified. Overall, the study suggests that AI-assisted feedback can serve as an effective supplementary tool for enhancing academic writing instruction in EFL contexts.